PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA LINGKUNGAN PADA NILAI PERUSAHAAN - Sutha, I Gusti Ngurah Dwi Parama; Widanaputra, Anak Agung Gde Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Firm value is an investor's perception of the company's level of success which is often associated with stock prices. High stock prices make the value of the company also high. A high company value will make investors not only believe in the company's current performance but also in the company's prospects in the future. This study aims to analyze the effect of good corporate governance and environmental performance on firm value. This research was conducted on mining companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This study uses secondary data, namely from the annual reports of mining companies on the IDX for the 2016-2020 period. Data were collected using purposive sampling technique with a number of observations of 30 companies. Data were analyzed using multiple linear regression. The results of this study can show that good corporate governance and environmental performance have a positive effect on the value of mining companies listed on the Indonesia Stock Exchange in 2016-2020. The implication of this research is that GCG and environmental performance provide a positive signal for investors in assessing the performance of a company. In addition, the company also strives to align its economic goals with its social goals in order to pay more attention to the environment so that it will be accepted by the community and the company has good prospects in the future.